Exposure to hot and cold environments increases noradrenaline release in the bed nucleus of the stria terminalis in rats - Saki Minami; Hiroshi Nomura; Masabumi Minami (Wiley, 2018)
Abstract Aims Thermoregulatory responses in homeothermic animals, including humans, are classified into involuntary autonomous and voluntary behavioral thermoregulatory responses. Although behavioral thermoregulatory responses are probably driven by positive (pleasant) and/or negative (unpleasant) emotions, the neuronal mechanisms underlying the induction of negative emotions by hot and cold environments remain poorly understood. The bed nucleus of the stria terminalis is a brain region implicated in stress responses and negative emotions, such as fear, anxiety, and aversion. Various stimuli that cause negative emotions, such as immobilization stress, fox odor, gastric distension, and inflammatory pain, increase noradrenaline release in the rat bed nucleus of the stria terminalis, especially in the ventral bed nucleus of the stria terminalis. It has been reported that the negative emotional component of pain is mediated by noradrenergic neurotransmission in the ventral bed nucleus of the stria terminalis. However, the role of intra‐ventral bed nucleus of the stria terminalis noradrenergic neurotransmission in the induction of negative emotion by exposure to hot and cold environments remains to be elucidated. For the first step to address this issue, the effects of hot and cold environments on noradrenaline release in the ventral bed nucleus of the stria terminalis were examined. Methods In vivo microdialysis analyses in unanesthetized, freely moving male Sprague‐Dawley rats were performed to examine hot and cold environments‐induced noradrenaline release in the ventral bed nucleus of the stria terminalis. Results Exposure to hot (38°C) and cold (8°C) environments significantly increased noradrenaline release in the ventral bed nucleus of the stria terminalis. Conclusions The results suggest that exposure to hot and cold environments enhances noradrenergic neurotransmission in the ventral bed nucleus of the stria terminalis, which may induce negative emotion, and thereby drive avoidance behaviors, that is, escape from hot and cold environments.